-5m+9=-51

Simple and best practice solution for -5m+9=-51 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5m+9=-51 equation:


m in (-oo:+oo)

9-5*m = -51 // + 51

9-5*m+51 = 0

60-5*m = 0 // - 60

-5*m = -60 // : -5

m = -60/(-5)

m = 12

m = 12

See similar equations:

| -7n-6=-69 | | 2k-7=9 | | -6b+1=-53 | | -2d-9=-13 | | 3+4k=-33 | | 2+4m=2 | | 1-3m=-26 | | 5x(3x-2)=0 | | -8-6m=-80 | | -4d-8=-52 | | 7d+4=-24 | | -6t-10=-34 | | 1(x)=2x-1 | | 2n-6=-16 | | 1+7x=-83 | | -6m-7=-31 | | 4-2n=-14 | | 2n+9=-9 | | -3a+7=19 | | 4n+1=-3 | | 5m+10=15 | | 3t+3=-21 | | -4k+1=-15 | | 2d-6=14 | | -7n-2=-44 | | 4+4n=-32 | | 5d+3=33 | | -7+5w=-7 | | 2t-6=14 | | 3w+9=33 | | 7-4d=39 | | -6b-7=-49 |

Equations solver categories